2015
DOI: 10.5152/akd.2014.5558
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between atrial electromechanical delay and left atrial mechanical function in stroke patients

Abstract: Objective:The aim of this study was to evaluate the relationship between atrial electromechanical delay (EMD) measured with tissue Doppler imaging (TDI) and left atrial (LA) mechanical functions in patients with ischemic stroke and compare them with healthy controls.Methods:Thirty patients with ischemic stroke were enrolled into this cross-sectional, observational study. The control group consisted of 35 age- and gender-matched apparently healthy individuals patients. Acute cerebral infarcts of probable emboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 30 publications
3
15
0
Order By: Relevance
“…Results of ours were consistent with, and supportive of, those in these previous studies [7,8]. Among patients with prior ischemic stroke, the clinical background similar to our MRFs patients, AEMD was shown to be prolonged (not as much prolonged as in AF patients) compared with normal controls [13] Potential mechanisms of prolonged AEMD in AF Longer AEMD implies more heterogeneous propagation impulse within the atria compromised by fatty replacement [17]. Although no experimental evidence has existed on this assumption, prolonged atrial conduction time is found to be associated with increased LA diameter and reduced LA systolic function, supporting the notion that AEMD reflects structural and electrophysiological remodeling of the atrium [18][19][20].…”
Section: Previous Studies On Aemd and Afsupporting
confidence: 91%
See 1 more Smart Citation
“…Results of ours were consistent with, and supportive of, those in these previous studies [7,8]. Among patients with prior ischemic stroke, the clinical background similar to our MRFs patients, AEMD was shown to be prolonged (not as much prolonged as in AF patients) compared with normal controls [13] Potential mechanisms of prolonged AEMD in AF Longer AEMD implies more heterogeneous propagation impulse within the atria compromised by fatty replacement [17]. Although no experimental evidence has existed on this assumption, prolonged atrial conduction time is found to be associated with increased LA diameter and reduced LA systolic function, supporting the notion that AEMD reflects structural and electrophysiological remodeling of the atrium [18][19][20].…”
Section: Previous Studies On Aemd and Afsupporting
confidence: 91%
“…An increased left atrial (LA) volume index is also known as a strong predictor of AF [3][4][5]. It has been reported that the intra-and interatrial conduction time, that is, the atrial electromechanical delay (AEMD), is an index of reflecting pathological changes of the atria [6][7][8][9][10][11][12][13]. AEMD can be measured not only by invasive electrophysiologic study but also by echocardiographic tissue Doppler imaging (TDI) [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Diastolic functions were also assessed by DDG because they were dependent on conventional doppler load and affected by heart rate. Previous studies have shown that E/Em ratio measured from septal annuler level is significantly correlated with left ventricular end-diastolic pressure and diastolic dysfunction (24). In our study, E / Em (septal) and E/Em (lateral) values were significantly increased in the SCI group.…”
Section: Discussionsupporting
confidence: 60%
“…Atrial electromechanical coupling (PA), the time interval from the onset of the P-wave on the surface electrocardiogram to the beginning of the late diastolic wave (A), was obtained from the lateral mitral annulus (PA lateral), septal mitral annulus (PA septal), and tricuspid annulus (PA tricuspid) ( Fig 1 ). The difference between PA lateral and PA tricuspid was defined as the interatrial electromechanical delay (EMD); the difference between PA septal and PA tricuspid was defined as the intra-right atrial EMD; and the difference between PA septal and PA lateral was defined as the intra-left atrial EMD [ 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%